Simulação das alterações hidrológicas ocasionadas por barramentos hidrelétricos na Bacia do Alto Paraguai - Melo, Maria Marcella Medeiros (2019)
The Brazilian energy matrix is mainly composed by hydraulic sources and, considering potential expansion scenarios, it is necessary the prior knowledge of its impacts for planning purposes. The Upper Paraguay River Basin (UPRB), where Pantanal is located, has dozens of hydroelectric plants in the plateau area, which may result in several impacts on the biome. This study aims to evaluate the effects of the hydropower plants operation located upstream of the UPRB on the flow regime and inundation patterns of Pantanal. Hypothetical scenarios were developed to investigate the effect of Manso hydropower plant and also the impact of all existing and planned hydroelectric plants in the basin, besides Manso. Using boundary conditions obtained by simulation on the plateau region, SIRIPLAN model was applied to simulate Pantanal hydrological processes. The quantification of the changes was performed using the Indicators of Hydrological Alteration (IHA) and different approaches of the Variability Range Approach (RVA), moreover, an adaptation was suggested for the traditional methodology. The results show that Manso has a strong regularization effect, significantly changing most of the indicators, with a predominant increase of minimum flows of different durations, and decrease of maximum flows and number of low pulses. In its turn, the reduction of the maximum flows reduced the frequency of flooding and average water depth around Cuiabá and Pantanal rivers. On the other hand, the operation of all hydroelectric plants resulted in minor changes with greater impact on the number and duration of low pulses. The combined operation seems to intensify drought conditions, decreasing the minimum flows of different durations, the median of drought months and increasing the duration of low pulses. When it comes to flooded area, the predominant behavior was also reduction, especially at the upper reaches of both Paraguay and Taquari rivers, which can intensify the silting in the region. The proposed adaptation for the traditional methodology resulted in minor changes of the indicators, more realistic than the traditional approach, although it has been observed little effect on the indicators related to high and low pulses. The RVA analysis considering the three categories (high, middle and low) was more satisfactory to represent the changes when compared to the traditional methodology. The results obtained demonstrated the interrelationships existing between different parts of Pantanal due to the lateral exchanges and that even located hundreds of kilometers away, the hydroelectric plants installed in the plateau has effect on its flow and flood regime.